The Effort of Beef Needs Supplying for Coming Years in Indonesia - Supardi Rusdiana; Ismail Ismail; Rusli Sulaiman; Amiruddin Amiruddin; Razali Daud; Zainuddin Zainuddin; Mustafa Sabri (The Faculty of Veterinary Medicine of Syiah Kuala University, 2018)
The increase in beef production is constrained by the slow growth of beef cattle population which is caused by the cattle breeding business that is considered less commercially profitable. The supplying of beef needs in a critical and effective manner is always increasing each year, so the price of beef is fluctuate. The various priority concept of the government's main program for the development of beef cattle is always done in every region in Indonesia. But the production of beef is still less and the government have to import the beef to fulfill the beef production. Therefore, this issues need necessary operational steps to provide more open space for some factors and leverage points in the supplying of beef needs. The purpose of this review is to examine the efforts to supply beef needs for the future in Indonesia critically. The high price of beef is not a mistake of the government. Basically, the government has tried to make the beef cattle population increased, to fulfill the consumer needs and the prices of beef is affordable for the customer. To cope with the higher beef prices, the government is make a policy of developing small, medium-sized, and big beef cattle breeding industries through seed cattle spreads on plantations of oil palm, rubber and cultivable fields for the development of beef cattle population. It is expected that in the coming year, beef cattle business can be oriented to agribusiness bussiness so that farmer's welfare will increase and can support Indonesia as the world food granary.